RAAIS: Rapid Appraisal of Agricultural Innovation Systems (Part II); integrated analysis of parasitic weed problems in rice in Tanzania - Schut, Marc; Rodenburg, J.; Klerkx, Laurens; Kayeke, J.; Ast, A. van; Bastiaans, L. (Elsevier, 2015)
Parasitic weeds such as Striga spp and Rhamphicarpa fistulosa in smallholder rice production systems form an increasing problem for food and income security in sub-Saharan Africa. In this paper we implement the Rapid Appraisal of Agricultural Innovation Systems (RAAIS) as a diagnostic tool to identify specific and generic entry points for innovations to address parasitic weeds in rain-fed rice production in Tanzania. Data were gathered across three study sites in Tanzania where parasitic weeds are eminent (Kyela, Songea Rural and Morogoro Rural districts). The results demonstrate that in Tanzania, weeds in general and parasitic weeds in particular receive little attention in agricultural research, training and education curricula. Crop protection policies mainly focus on the control of (insect) pest and diseases and there is relatively little attention for weed prevention, which is essential for addressing parasitic weed problems effectively. Specific entry points for innovation include increasing awareness of parasiticweed problems among farmers, extension and crop protection officers and policymakers. In regions where awareness is relatively high, participatory research approaches can provide a basis for developing locally adapted parasitic weed management strategies. Generic entry points for innovation include enhanced collaboration and interaction between stakeholders across different levels, for example in multi-stakeholder platforms. This can provide the basis for developing and implementing coherent policy and development strategies to address structural constraints in the agricultural system, including the promotion of clean local seed systems, investments in physical and knowledge infrastructure development, adequate backstopping of agricultural extension officers, agribusiness training for farmers, quality control of agricultural inputs, timely access to agricultural inputs, and improved access to markets for farmers. Together the specific and generic entry points can strengthen the innovation capacity of Tanzania’s agricultural system to address parasitic weed problems, as well as other complex agricultural problems.